Examination of relation between high school students' online game addiction, loneliness, aggression and depression tendency - Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem; Kılıç, Ahmet Emre; Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem (My University, 2018)
Playing online games is one of the most popular Internet activities of our time. With the widespread use of the Internet, interest in online games has also increased. While it is formerly mostly limited to game centers, online gaming habits can now be maintained at any time of day thanks to the smartphones. One of the reasons why interest in online games increased is online games of nowadays render the possibility of playing with multi-player. Apart from online game playing, this interest also proceeds on virtual social groups through social network activities such as sharing videos of games they play, discussion of them, learning new strategies. Although online games have cognitive, emotional, motivational and social benefits, they also lead to undesirable situations like game addiction. Therefore, it should be taken into account that online game addiction can bring about many physical, mental and psychological problems. In the researches carried out, online game addiction leads excessive anxiety, intolerance, hasty behavior, anger, mood swings, and behavioral changes. For this reason, determining the factors associated with online gaming addiction may be a guide to preventing addiction. The aim of this research is to examine the online game addiction status of high school students and to examine the relationship of online game addiction and feeling of loneliness, aggression and depression tendencies. The research was carried out according to the correlational research model and was conducted on the students of an Anatolian High School located in a province center in the Western Black Sea Region. Participants of this study consist of 276 high school students. Data of study; Online Game Addiction Scale that is to determine addiction status of high school students, the UCLA Loneliness Scale that is to determine students' loneliness status, BUSS-PERRY Aggression Scale that is to determine students' aggression tendencies, BECK Depression Scale that is to determine students' depression tendencies. It has been questioned whether the data obtained within the scope of the study can meet the normal assumptions; as a result it has been seen data is normally distributed. Findings from the researches are; there is a low positive significant correlation (r = .26; p <.01) between high school students' online game addiction and their feeling loneliness, there is a moderately positive significant correlation (r = .44; p <.01) between online game addiction and aggression tendencies, there is a low positive significant correlation (r = International Child and Information Safety Congress "Digital Games" April 11-13, 2018-Ankara, TURKEY FULL TEXT BOOKLET 134 .28; p <.01) between online game addiction and depression tendencies. When the relations of other scales are examined; it has been seen, there is a moderately positive significant correlation between feeling loneliness and aggression tendencies (r = .47; p <.01), there is a low significant positive correlation between depressive tendencies and feelings of loneliness (r=.15; p<.01), there is moderately positive significant relation between depression tendency and aggression tendency (r=.34; p<.01). According to findings obtained from the research, due to the increase of online gaming addiction it can be said, students' feeling loneliness increased a bit, their aggression behaviour increased and depression tendency an increased a bit. In reducing online game addiction; taking preventative measures can be taken to decrease online game playing addiction and to reduce addicted user's feelings of loneliness, their tendency to engage in depression and aggression tendencies. It was discussed what can be done in order to decrease the game addiction of the students in the direction of the findings obtained from the research. Various suggestions have been given to teachers, parents and policy makers.
Keywords: Loneliness; Aggression; Depression tendency; High school students; Online game addiction; Game addiction